Research on Collaborative Relationships with Parents of Young Children with Distinctive Characteristics such as Developmental Disorders: A Study on the Transformation Process of the Feelings of Parents - Sasaki, Sawako (Japanese Journal of Child and Family Welfare, 2020)
The aim of this study was to investigate the transformation process of the feelings of parents in relation to collaborative staff-parent relationships, with parents who care for young children with distinctive characteristics, such as developmental disorders. The method of study involved interviewing parents of these young children and the nursery school teacher in charge of their care. Analysis was performed based on the Trajectory Equifinality Approach (TEM). The results found that there was a significant relationship between “obtaining a consensus of feelings,” “reconstructing reality in terms of recognition of the target child” and “learning by the nursery school teacher themselves, rather than just supporting the parent,” and the development of collaborative parent-teacher relationships. By reconstructing the reality of the child grasped by the parent and nursery school teacher, it was suggested that support could be provided to the parent, leading to the stabilization of their feelings. Additionally, the nursery school teacher is in the position of learning from the parent in relation to the care of the child, and it was found that mutual learning is necessary for the development of this collaborative relationship.